EFFECT OF ADDING GARDEN CRESS (LEPIDIUM SATIVUM) ON RUMEN FERMENTATION OF LOCAL AWASSI LAMBS - Abbas, Mohammed Hameed; Shwayel, Mohammed Ahmed (Journal of agricultural, environmental and veterinary sciences, 2019)
This study was to study the effect of adding Lepidium sativum to the lamb diets of Awassi sheep. Nine male lambs (their age is 3 months old and their body weight is 19±0.5 Kg) were distributed randomly into 3 treatments (3 lambs per treatment). The coarse feed (hay) was provided freely to lambs, while the concentrated feed was provided based on 3% of the body weight. All treatments were fed on similar diet and differed only in the weight of seeds, where 7.5 g was added to the second treatment (T2) and 15 g of Garden Cress to the third treatment (T3) while the control treatment (T1) left without adding seeds. The experiment continued for 60 days. The results showed a significant increase in pH at 0 hour in treatments T2 and T3 with Garden Cress of 7.5 and 15 g respectively, but there was a significant decrease at 3 hours in treatment T3 and also at 6 hours in T2 and T3 as well. For total phenols there was a decrease at 6 hours in treatment T2.When adding Garden Cress to concentrated rations, it did not significantly affect N-NH3, but improved somewhat of rumen fermentation and microorganism’s numbers at 3 hours for T2 and T3 with Garden Cress of 7.5 and 15 g respectively. There was a significant increase in fatty acids at 6 hours in T2 and T3 while there was no significant effect at other times and treatments.